A new cytometry-based method reveals an accumulation of Nrf2 in dendritic cells exposed to two respiratory sensitizers. Issue 6 (26th November 2021) - Audry, Adrien; Mathiot, Julianne; Muller, Samuel; Coiscaud, Amélie; Langonné, Isabelle; Battais, Fabrice; Leininger, Brigitte; Sponne, Isabelle
Abstract: The mechanisms underlying chemical respiratory sensitization are incompletely understood. One of the major cell types involved in this pathology are dendritic cells. In this study, the mechanisms of the NRF2–Keap1 pathway were studied using a bone marrow-derived dendritic cell model exposed to two respiratory sensitizers: ammonium hexachloroplatinate (HCP) and ammonium tetrachloroplatinate (ATCP). Expression levels for two Nrf2-regulated genes, hmox1 and srxn1, were analyzed by real time-quantitative polymerase chain reaction. A flow cytometry-based method was also developed to measure intracellular Nrf2 accumulation in dendritic cells following exposure. Exposure to HCP and ATCP increased both hmox1 and srxn1 gene expression, and was associated with accumulation of Nrf2 protein in cells. Overall, these results show that the respiratory sensitizers, in addition to skin sensitizers, can also induced markers associated with NRF2–Keap1 pathway activation in dendritic cells. This study contributes to a better understanding of the adverse outcome of respiratory sensitization.